Knowledge and Innovation as a Condition for the Progress of Society: Challenges, Opportunities, Development Trends (Laisvalaikio tyrimai, 2022)
The relevance of the research topic is that the rapid expansion of scientific knowledge is a key factor in maintaining the development of the progress of society. Technological innovation, measured as a result of rapid increases in wealth, is becoming an important tool in the development of as yet unavailable resources. Social media, mobile communications, and big data technologies are key components of collaboration between non-state actors and governments.The purpose of the study is to conceptualize knowledge and innovation as a condition for the progress of socio-political and economic development of society.Research objectives: 1. analysis of the development of information technology as a new trend that affects the development of the modern world; 2. the formation of human capital as a condition for the progress of the socio-political and economic development of society; 3. a progressive scenario of the socio-political and economic development of society; 4. the formation of a creative class as a factor in the development of information and communication technologies.Research methods: Observation and fixation in terms accepted in science, the most significant features, manifestations of the development of society; systematic generalization of a variety of empirical data, information reflecting various aspects and states of the object; analysis and synthesis of information, the method of consistency, which helped to lead to the integrity of the investigated object.Research result: It has been proven that information technology is entering the era of big data. Operational processes and data banks are becoming almost free; web and cloud technologies provide global access and ubiquitous services; social media and cyber security are emerging as big new markets. Three technological directions are changing our way of life, the way we do business and security: technologies in the field of storage and processing of large amounts of data; social networking technologies; “Smart cities” as a multitude of urban technologies working with updated and secure IT systems. Advances in big data storage and processing herald an imminent economic boom, advances in a variety of technologies are shaping giant investments in smart city infrastructure.Key words: knowledge, innovation, progress, information and computer technologies, human capital, creative class.